Do Sublaminar Polyester Bands Affect the Outcomes of Postoperative Infections After Adolescent Idiopathic Scoliosis Surgery?. Issue 8 (December 2017) - Issa, Samir P.; Angelliaume, Audrey; Vidal, Christophe; Mazda, Keyvan; Ilharreborde, Brice
Abstract : Background: The incidence of surgical site infections (SSI) after adolescent idiopathic scoliosis (AIS) surgery ranges from 0.5% to 7%. There is currently a regain of interest in hybrid constructs, combining lumbar pedicle screws and thoracic sublaminar bands, but some authors have raised concerns about the risk of SSI and the difficulty of bacterial eradication. The goal of this study was therefore to assess the outcomes of SSI after AIS surgery using sublaminar bands. Methods: A total of 524 consecutive patients operated for AIS using sublaminar bands between June 2006 and June 2014 were included. SSI cases were identified and analyzed retrospectively. Radiologic and functional outcomes were evaluated at follow-up using EOS imaging and SRS 30 scores, and compared with a control group. Results: The overall SSI rate was 5.3%, with a majority of monomicrobial (86%) infections occurring in the first 6 weeks postoperative (93%). The most frequent pathogens were skin germs ( Staphylococcus aureus and Propionibacterium acnes ) with a community profile. Patients were treated successfully with surgical debridement without implants removal, associated with 6 weeks of antibiotherapy. However, 25% of patients required >1 surgical debridement. Instrumentation removal was decided in the 2 cases with late SSI, and performed uneventfully. Radiologic and functional outcomes at follow-up were not affected by the occurrence of SSI. Conclusions: Sublaminar bands are not associated with a higher risk of infection. However, the SSI rate in the current study stands in the upper range of the literature, and other preventive strategies should be considered. In case of early infection, bands removal is not necessary to obtain pathogen eradication, but the sublaminar implants can be pulled out safely in case of late SSI. The occurrence of SSI does not alter the outcomes at follow-up. Level of Evidence: Level III.